Problematika Lingkungan Sosial dalam Pembentukan Karakter Siswa Sekolah Dasar di Indonesia: A Systematic Literature Review - Annisah Diana Syafitri; Husnia Kaisyah; Jihan Badzlina; Mhd Gagah Prajaya; Khairunnisa Khairunnisa (Jurnal Keluarga Sehat Sejahtera, 2026)
The social environment is a crucial factor influencing the character development process of elementary school (SD) students. Various problems within the social environment including family dynamics, peer interactions, school culture, community involvement, and digital technology exposure potentially hinder the optimal internalization of character values. This study aims to identify, analyze, and synthesize findings from previous research (2020–2025) on the problems of the social environment in the character formation of elementary school students in Indonesia. The method employed is a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Literature searches were conducted through Google Scholar, ERIC, and Garuda databases using structured keywords. A total of 20 articles meeting the inclusion criteria were critically analyzed. The results show that a dysfunctional social environment whether in the family, school, or community domain significantly contributes to the weakening of elementary students' character, reflected in increased aggressive behavior, low empathy, discipline crises, and declining learning motivation. These findings underscore the importance of collaboration among the three pillars of education family, school, and community to create a social ecosystem conducive to the growth of noble student character. This article contributes to the development of an integrative model of character formation based on the social environment at the primary education level.